Energy and Sustainable Futures Proceedings of 2nd ICESF 2020 - Mporas, Iosif; Kourtessis, Pandelis; Al-Habaibeh, Amin; Asthana, Abhishek; Vukovic, Vladimir; Senior, John (Springer Proceedings in Energy,, 2021)
This open access book presents papers displayed in the 2nd International Conference on Energy and Sustainable Futures (ICESF 2020), co-organised by the University of Hertfordshire and the University Alliance DTA for Energy. The research included in this book covers a wide range of topics in the areas of energy and sustainability including: • ICT and control of energy; • conventional energy sources; • energy governance; • materials in energy research; • renewable energy; and • energy storage. The book offers a holistic view of topics related to energy and sustainability, making it of interest to experts in the field, from industry and academia.